Public and private pension systems and macroeconomic volatility in OECD countries - Holzner, Mario,Jestl, Stefan,Pichler, David (Wiener Institut für Internationale Wirtschaftsvergleiche, 2019)
This paper analyses the impact of public pension expenditures and pension funds' assets as well as their benefits on economic volatility. To do so, we use panel data for 35 OECD countries for the period 1980-2018 and apply a set of state-of-the-art econometric estimators. Our results show weak evidence of a negative impact of public pension expenditures as well as weak evidence of a positive impact of pension funds' benefits on volatility. Results were, however, found not to be very robust. In contrast, pension funds' assets do not show any evidence of being associated with economic volatility. Unsystematic fiscal policy, banking crises and political (in)stability, however, are revealed to be somewhat more robust determinants of economic volatility.
10419/223077
Keywords: Graue Literatur; Public pensions; private pensions; pension system; macroeconomic volatility; OECD